Light Quantity Affects the Regulation of Cell Shape in Fremyella diplosiphon - Pattanaik, Bagmi; Whitaker, Melissa J.; Montgomery, Beronda L. (Frontiers in Microbiology, 2012)
In some cyanobacteria, the color or prevalent wavelengths of ambient light can impact the protein or pigment composition of the light-harvesting complexes. In some cases, light color or quality impacts cellular morphology. The significance of changes in pigmentation is associated strongly with optimizing light absorption for photosynthesis, whereas the significance of changes in light quality-dependent cellular morphology is less well understood. In natural aquatic environments, light quality and intensity change simultaneously at varying depths of the water column. Thus, we hypothesize that changes in morphology that also have been attributed to differences in the prevalent wavelengths of available light may largely be associated with changes in light intensity. Fremyella diplosiphon shows highly reproducible light-dependent changes in pigmentation and morphology. Under red light (RL), F. diplosiphon cells are blue-green in color, due to the accumulation of high levels of phycocyanin, a RL- absorbing pigment in the light-harvesting complexes or phycobilisomes (PBSs), and the shape of cells are short and rounded. Conversely, under green light (GL), F. diplosiphon cells are red in color due to accumulation of GL- absorbing phycoerythrin in PBSs, and are longer and brick-shaped. GL is enriched at lower depths in the water column, where overall levels of light also are reduced, i.e., to 10% or less of the intensity found at the water surface. We hypothesize that longer cells under low light intensity, which is generally enriched in green wavelengths, are associated with greater levels of total photosynthetic pigments in the thylakoid membranes. To test this hypothesis, we grew F. diplosiphon under increasing intensities of GL and observed whether the length of cells diminished due to reduced pressure to maintain larger cells and the associated increased photosynthetic membrane capacity under high light intensity, independent of whether it is light of green wavelengths.